The role of the Human Resources Coordinator in Big Four Companies: Introduction to the Government of Behavioral Psychology - de Nichilo, Stefano (Journal of Applied Research and Multidisciplinary Studies, 2021)
The HR coordinator is a new professional figure in the field of personal education and social and behavioral psychology. This paper analyzes the factors that explain the increased use of special reports in Big Four, wondering if they look like evaluation studies. In Big Four auditing firms characterized by strong institutional activism and social dialogue, the HR Coordinator, without performing any function of intermediation of projects or information, has had great success in not creating contrasts or obsessive quarrels by implementing programmed methodologies on social inference. It examines their training as well as their impact as well as the institutional use implicit in the performance audit. The picture of the staff employed in the company and its management over time give an evident measurement of the company’s strategic and intellectual capacities. From an anthropological perspective, the audit could traditionally be considered as "Rituals of Verification", recognizing the procedure and the evaluation have social effects, in public management. It is a success of educational pedagogy and organizations settings methodologies. However, the performance established a regulatory dimension compared to the concept of verification.